The Network Structure of Adolescent Well-Being Traits: Results From a Large-Scale Chinese Sample - Zeng, Guang (Front Psychol, 2019)
Background: The mental health and well-being of adolescents are becoming increasingly important globally. Understanding the relationship between different aspects of well-being is crucial for effective interventions of the well-being of adolescents. The present study aims to analyze the network structure of adolescent well-being and identify the central well-being traits. Methods: We used a network model to analyze the network structure of a psychometrically sound measurement of adolescent well-being – the engagement, perseverance, optimism, connectedness, and happiness (EPOCH) scale. The dataset comes from a representative sample of Chinese adolescents (17, 854 participants from rural and urban areas from Southern, Northern, and the middle part of China). Results: The 20 items of EPOCH formed a highly interconnected network. The item H4 (“I am a cheerful person.”), item E2 (“I get completely absorbed in what I am doing”), and item O4 (“I believe that things will work out, no matter how diffcult they seem”) were the traits with the highest centrality in the network. Conclusions: Cheerfulness, engagement in current activity, and optimism for the future are most central to the psychological well-being of Chinese adolescents. Future studies should further test the dynamics between these central traits and other well-being traits to find effective interventions of well-being of adolescents.